Exploring the Emerging Church - Po, SFL (2020)
Since the 1960s, church attendance has been steadily declining in both the United Kingdom and the United States. Simultaneously, the number of individuals who claim ‘no religion’ – known as the ‘nones’ – is rising. Come the late 1990s, the term ‘emerging-’ or ‘emergent church’ began to circulate around Nondenominational Christian discourses in the United States, and soon became an indefinable, but recognisable, concept within contemporary Christianity. In 2004, inspired by the Emerging Church and as a response to the decline in church attendance, the Church of England and the Methodist Church collaboratively published a report titled Mission-shaped Church, initiating a movement for the creation of Emerging Church-like groups called Fresh Expressions in the United Kingdom. Today, despite being a popular, if not influential, concept in both the United Kingdom and the United States, very little comprehensive social scientific research has been done on the Emerging Church, not to mention remaining ambiguous in definition. Furthermore, it is not unusual for participants of the Emerging Church to have ambiguous religious identities either—this reflects characteristics of both Christianity and the New Age, or what I call Self-religion. In this research, I aim to demonstrate, through its most deeply held value, the core identity of the Emerging Church: inclusivity. This value of inclusivity is observable from experiences of pain, conflict, and trauma, and is what provides the feeling of belonging and the experience of community. It has its own specific parameters, such as having a relationship to established Christianity, as well as requiring a basic interest in spirituality, making it a sacralised value. I then compare this identity to Christianity and the Self-religion. The Emerging Church, conceived in this way, provides implications to the wider religious landscape of the decline in church attendance and rise of religious ‘nones’, as well as Christianity and Self-religion: it is relevant to Christianity because it demonstrates the reasons why some people stop attending church, and ways in which it might respond to this information. It also relevant to Self-religion as it demonstrates that it is not a phenomenon that is restricted to alternative religion, and that religious ‘nones’ are not necessarily unreligious.